Anti-fading plastic pigment and preparation method thereof
By using tungstate or titanate as the basis in plastic pigments and introducing coordinated doping of rare earths and transition metal ions, the stability of existing pigments in high temperature and ultraviolet environments is solved, and high-performance plastic pigments are achieved.
Patent Information
- Application Number
- CN202411913896.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-18
AI Technical Summary
Existing plastic pigments have shortcomings in high temperature stability, UV resistance, dispersion and environmental protection, and are difficult to meet high performance needs.
Based on tungstate or titanate, rare earths and transition metal ions are synergistically doped, and through an optimized atmosphere calcination process, a stable solid solution structure is formed to improve the thermal stability and ultraviolet resistance of the pigment.
It significantly improves the thermal stability and UV resistance of the pigment, ensures the color stability in high temperature and ultraviolet environments, and is suitable for the coloring of high-performance plastic products.
Smart Images

Figure CN119638405A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pigment preparation, in particular to an anti-fading plastic pigment and a preparation method thereof. Background Art
[0002] With the widespread application of plastic products in industry and daily life, the appearance quality and service life of plastics have gradually become important research directions. Color is an important appearance characteristic of plastic products, and its long-term stability directly affects the visual effect and market competitiveness of the product. In order to achieve uniform coloring of plastics, the selection and performance of pigments are particularly critical. However, existing plastic coloring pigments generally have problems such as poor high temperature resistance, insufficient light aging resistance, poor dispersibility, and lack of environmental friendliness.
[0003] The processing of plastic products usually needs to be completed under high temperature conditions, especially the processing temperature of engineering plastics (such as polyphenylene sulfide PPS, polyetheretherketone PEEK, etc.) is usually over 300℃. Traditional pigments are prone to decomposition, oxidation or chemical structure changes at such high temperatures, resulting in color distortion or even failure. In addition, many plastic products need to be exposed to ultraviolet rays, oxygen and other harsh environments for a long time, which puts higher requirements on the anti-light aging performance of pigments. Most traditional pigments are prone to photodegradation under long-term ultraviolet radiation, which manifests as fading, whitening or even powdering, seriously affecting the appearance quality and service life of plastic products.
[0004] In the actual application of plastic products, the dispersibility of pigments is also a key performance indicator. Good dispersibility can make the pigment evenly distributed in the plastic matrix, thereby achieving uniform coloring and improving the overall quality of the product. However, some pigments are prone to agglomeration in plastics due to irregular particle morphology or uneven particle size distribution, resulting in uneven coloring and even affecting the mechanical properties of the product.
[0005] In addition, with increasingly stringent environmental regulations, the environmental friendliness and safety of pigments have also become a focus of attention. Although some traditional pigments, such as lead-containing and chromium-containing pigments, have excellent performance, their use is gradually being restricted due to their potential harm to the environment and human health. This puts higher demands on the development of environmentally friendly, non-toxic, high-performance plastic pigments.
[0006] Therefore, there is a strong demand in the market for a plastic pigment that can meet the requirements of high temperature stability, light aging resistance, good dispersibility, and environmental protection and non-toxicity. However, the types of pigments and preparation processes in the existing technology still cannot achieve a comprehensive balance in these performance dimensions. This field urgently needs a breakthrough solution to meet the high performance requirements of the plastics industry. Summary of the invention
[0007] In view of the deficiencies in the prior art, the present invention provides an anti-fading plastic pigment and a preparation method thereof, which solve the deficiencies in high temperature stability, UV resistance, dispersibility and environmental protection of the prior plastic pigments.
[0008] To achieve the above objectives, the present invention is implemented through the following technical scheme: an anti-fading plastic pigment, comprising the following components by weight percentage: 70%-90% tungstate or titanate, 3%-10% rare earth doping ions, 2%-8% transition metal doping ions, 5%-15% citric acid, 1%-5% ammonia water, and the rest is solvent deionized water.
[0009] Preferably, the tungstate is sodium tungstate, and the titanate is barium titanate.
[0010] Preferably, the rare earth doping ions are cerium nitrate and praseodymium nitrate, and the transition metal doping ions are iron nitrate and nickel nitrate.
[0011] Preferably, the rare earth doping ions and transition metal doping ions are mixed in a molar ratio of 1:1, and the total doping amount is 5%-10% of the total molar amount of tungstate or titanate.
[0012] A method for preparing an anti-fading plastic pigment comprises the following steps: S1. Preparation of precursor solution: dissolve tungstate or titanate in deionized water, add citric acid chelating agent, stir for 50-60 minutes to form a basic solution, slowly add rare earth doping ion and transition metal doping ion solution, and stir evenly; S2, co-precipitation: add ammonia water to the mixed solution, adjust the pH to 8.5-9.0, control the temperature to 70-80°C, form a precipitate, and age the precipitate for 6-12 hours; S3, drying and calcining: drying the precipitate to form a precursor powder, which is then calcined in two stages to form the final pigment particles; S4. Pigment preparation: The calcined pigment particles are refined to 100-500 nm by wet ball milling, the ball milling medium is ethylene glycol, and the ball milling time is 2-4 hours.
[0013] Preferably, during the preparation of the precursor solution in step S1, the rare earth doping ion solution and the transition metal doping ion solution are added to the base solution in a dropwise manner, with a dropwise acceleration rate of 0.5-1 mL / min and a stirring temperature of 60-70°C.
[0014] Preferably, in the co-precipitation step of step S2, the concentration of the aqueous ammonia solution is 20-25%, and the precipitation aging is carried out in a water bath at 50-60°C.
[0015] Preferably, the drying in step S3 is performed at 80-90° C. for 10-12 h.
[0016] Preferably, the roasting in step S3 includes: The first stage: calcination at 300-400℃ for 1-2h; The second stage: calcining at 700-800℃ for 4-5h, while introducing a 10%-15% oxygen and nitrogen mixed gas.
[0017] According to any one of claims 1 to 4, the anti-fading plastic pigment is used for high-temperature processing coloring of polypropylene, polyamide, polyphenylene sulfide, and polyetheretherketone-based plastics and coloring of UV-resistant plastic products.
[0018] The present invention provides an anti-fading plastic pigment and a preparation method thereof. The invention has the following beneficial effects: 1. The pigment of the present invention is synergistically doped with rare earth and transition metal ions, and through an optimized atmosphere roasting process, the doped ions form a stable solid solution structure in the barium titanate or tungstate lattice, which significantly improves the thermal stability of the pigment. The high thermal stability of the rare earth ions and the lattice stability of the transition metal ions work together to enhance the anti-decomposition ability of the pigment crystal phase in a high temperature environment. At the same time, through high-temperature roasting and atmosphere control, the thermal expansion and lattice defects of the pigment particles are further suppressed, thereby effectively reducing the color change at high temperature.
[0019] 2. The present invention significantly enhances the absorption and shielding capabilities of ultraviolet light by introducing rare earth ions into the crystal lattice. Rare earth ions have unique optical properties and can absorb ultraviolet light through FD transition, reducing the damage of ultraviolet light to the molecular structure of the pigment. In addition, the introduction of rare earth ions can also improve the antioxidant properties of the crystal lattice, prevent the pigment from generating free radicals under ultraviolet irradiation, and further reduce the photoaging phenomenon of the pigment. Combined with the doping-optimized crystal phase design and the well-dispersed micron-sized particle structure, it can maintain color stability in a long-term ultraviolet light exposure environment, avoid fading or gloss reduction, meet the high-performance requirements of long-term use of automotive parts, building materials, etc., and show excellent anti-ultraviolet ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The present invention is a flow chart of the preparation method. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Please refer to the attached Figure 1The embodiment of the present invention provides an anti-fading plastic pigment, which includes the following components by weight percentage: 70%-90% tungstate or titanate, 3%-10% rare earth doping ions, 2%-8% transition metal doping ions, 5%-15% citric acid, 1%-5% ammonia water, and the rest is solvent deionized water.
[0023] Specifically, the pigment of the present invention uses tungstate or titanate as the basic lattice material. Such inorganic materials have excellent thermal stability and chemical inertness, and can maintain a stable crystal phase structure under high temperature conditions to avoid decomposition or denaturation, thereby providing an ideal lattice environment for the doping of rare earth and transition metal ions. At the same time, titanate has good optical properties and can synergize with doped ions to improve the color performance and UV resistance of the pigment, which is the key support for the performance of the pigment.
[0024] By introducing rare earth doping ions, the present invention significantly enhances the absorption and shielding ability of the pigment to ultraviolet rays. Rare earth ions have unique optical properties and can effectively absorb ultraviolet rays through FD transitions to prevent ultraviolet light from damaging the pigment structure. In addition, the high thermal stability of rare earth ions can also enhance the overall stability of the lattice, improve the pigment's ability to resist decomposition in a high temperature environment, and reduce the generation of free radicals during light aging, further extending the service life of the pigment.
[0025] The present invention further optimizes the optical and thermal properties of the pigment by adding transition metal doping ions. Transition metal ions can regulate the light absorption range of the pigment by changing the electronic structure in the lattice, improve the color vividness and saturation, and synergize with rare earth ions to further enhance the stability of the pigment lattice and reduce crystal phase defects in high temperature environments, thereby significantly improving thermal stability and UV resistance.
[0026] During the preparation process, citric acid, as a chelating agent, can form stable chelates with metal ions to prevent premature precipitation or agglomeration of doped ions, thereby ensuring that rare earth and transition metal ions are evenly distributed in the basic lattice. Citric acid also regulates the crystal growth process, improves particle morphology, and inhibits excessive crystallization, ultimately forming pigment particles with uniform particle size and good dispersion, laying the foundation for the high performance of the pigment.
[0027] Ammonia is used as a precipitant. By adjusting the pH value of the reaction system to an appropriate range (8.5-9.0), tungstate or titanate reacts with metal ions to form a uniform precipitation precursor. The precise control of the precipitation process not only avoids uneven distribution of metal ions, but also provides an ideal crystal precursor structure for the subsequent calcination stage, effectively improving the overall performance of the pigment.
[0028] Finally, deionized water is used as a solvent to ensure the purity and uniformity of the entire preparation system. Deionized water reduces the interference of impurities, ensures the integrity of the lattice structure, and improves the dispersibility of pigment particles, enabling them to be evenly distributed in the plastic matrix, meeting the strict requirements of industrial applications for high performance of pigments.
[0029] The tungstate is sodium tungstate, and the titanate is barium titanate.
[0030] The rare earth doping ions are cerium nitrate and praseodymium nitrate, and the transition metal doping ions are iron nitrate and nickel nitrate.
[0031] Specifically, the pigment of the present invention uses sodium tungstate and barium titanate as the basic lattice materials, wherein sodium tungstate provides excellent high temperature stability and can maintain chemical inertness and crystalline phase integrity under high temperature environment, while barium titanate has unique electrical and optical properties, which can effectively enhance the optical performance of the pigment, making it have high brightness and good light aging resistance. These two basic materials provide an ideal lattice structure for rare earth and transition metal doping, ensuring the stability of the pigment in complex environments.
[0032] The present invention introduces cerium nitrate (Ce 3+ ) and praseodymium nitrate (Pr 3+ ) as rare earth doping ions greatly improve the UV resistance of the pigment. Cerium nitrate effectively absorbs ultraviolet light through fd transition, preventing ultraviolet light from damaging the molecular structure of the pigment, while praseodymium nitrate further enhances the light stability and color performance of the pigment. The two rare earth ions work together to improve the thermal stability of the lattice and inhibit the generation of free radicals, thereby significantly improving the pigment's resistance to light aging, allowing it to maintain color stability in a long-term ultraviolet light exposure environment.
[0033] In addition, the present invention uses iron nitrate (Fe 3+ ) and nickel nitrate (Ni 2+ ) as transition metal doping ions, further optimizing the optical and thermal properties of the pigment. Ferric nitrate can adjust the color absorption range of the pigment, giving the pigment a higher color saturation, while nickel nitrate enhances the overall strength of the lattice and prevents the generation of lattice defects under high temperature conditions. The synergistic doping of ferric nitrate and nickel nitrate also improves the pigment's ability to resist decomposition under high temperature conditions and improves its tolerance to oxidative environments.
[0034] The rare earth doping ions and the transition metal doping ions are mixed in a molar ratio of 1:1, and the total doping amount is 5%-10% of the total molar amount of tungstate or titanate.
[0035] Specifically, rare earth and transition metal ion co-doping can form a uniformly distributed solid solution structure in the base lattice (tungstate or titanate). 3+ , Pr3+ ) have a large ionic radius and can effectively fill the gaps in the lattice, while suppressing crystal phase defects at high temperatures by enhancing the local stability of the lattice. Transition metal ions (such as Fe 3+ 、Ni 2+ ) enhances the optical absorption range and thermal decomposition resistance of the lattice through its unique electron orbital transition characteristics. Mixing rare earth and transition metal ions in a 1:1 molar ratio can ensure the balanced distribution of the two in the lattice, avoid local segregation or stress concentration, and thus improve the overall stability and functionality of the pigment.
[0036] A method for preparing an anti-fading plastic pigment comprises the following steps: S1. Preparation of precursor solution: dissolve tungstate or titanate in deionized water, add citric acid chelating agent, stir for 50-60 minutes to form a basic solution, slowly add rare earth doping ion and transition metal doping ion solution, and stir evenly; S2, co-precipitation: add ammonia water to the mixed solution, adjust the pH to 8.5-9.0, control the temperature to 70-80°C, form a precipitate, and age the precipitate for 6-12 hours; S3, drying and calcining: drying the precipitate to form a precursor powder, which is then calcined in two stages to form the final pigment particles; S4. Pigment preparation: The calcined pigment particles are refined to 100-500 nm by wet ball milling, the ball milling medium is ethylene glycol, and the ball milling time is 2-4 hours.
[0037] During the preparation of the precursor solution in step S1, the rare earth doping ion solution and the transition metal doping ion solution are added to the base solution in a dropwise manner, with a dropwise acceleration rate of 0.5-1 mL / min and a stirring temperature of 60-70°C.
[0038] In the co-precipitation step of step S2, the concentration of the aqueous ammonia solution is 20-25%, and the precipitation aging is carried out in a water bath at 50-60°C.
[0039] The drying in step S3 is carried out at 80-90° C. for 10-12 h.
[0040] The roasting step S3 includes: The first stage: calcination at 300-400℃ for 1-2h; The second stage: calcining at 700-800℃ for 4-5h, while introducing a 10%-15% oxygen and nitrogen mixed gas.
[0041] The pigment is used for high temperature processing coloring of polypropylene, polyamide, polyphenylene sulfide, polyetheretherketone based plastics and coloring of UV-resistant plastic products.
[0042] Embodiment 1: Material ratio: Barium titanate 80wt%, cerium nitrate 4wt%, praseodymium nitrate 2wt%, iron nitrate 3wt%, nickel nitrate 2wt%, citric acid 9wt%, ammonia water (25% concentration): 4wt%, and the balance deionized water.
[0043] Preparation process: S1: Precursor solution preparation Dissolve 8 g of barium titanate in 100 mL of deionized water; Add 9 g of citric acid and stir for 60 minutes to form a uniform basic solution; A solution of 2 g of cerium nitrate, 1 g of praseodymium nitrate, 1.5 g of iron nitrate and 1 g of nickel nitrate was added dropwise at a rate of 0.7 mL / min, and stirring was maintained at 60°C.
[0044] S2: Coprecipitation Add 4 g of ammonia water (25% concentration) to the base solution and adjust the pH to 8.8; Keep stirring at 70°C for 1 h to form a precipitate; Aging was carried out in a water bath at 50°C for 6 h.
[0045] S3: Drying and roasting Drying: Dry the precipitate in an oven at 85 °C for 12 h; Roasting: The first stage: calcination at 300℃ for 2h; The second stage: calcination at 700℃ for 4h, introducing a 10% oxygen-nitrogen mixed gas.
[0046] S4: Wet ball milling The calcined pigment particles were added to ethylene glycol and wet-milled for 2 h to a size of 200 nm.
[0047] Summary: This example prepares an anti-fading plastic pigment by optimizing the basic doping ratio and controlling the process. Using barium titanate as the basic lattice material, rare earth elements and transition metal elements are doped in basic proportions, stirring at 60°C, precipitating at 70°C, drying at 85°C, and two-stage calcination (300°C and 700°C), UV-resistant pigment particles with a particle size of 200nm are finally obtained. The pigment has good thermal stability and UV resistance, and is suitable for coloring ordinary high-temperature plastics.
[0048] Embodiment 2: Material ratio: Barium titanate 85wt%, cerium nitrate 3wt%, praseodymium nitrate 2wt%, iron nitrate 4wt%, nickel nitrate 3wt%, citric acid 8wt%, ammonia water (25% concentration) 3wt%, and the balance deionized water.
[0049] Preparation process: S1: Precursor solution preparation Dissolve 8.5 g of barium titanate in deionized water, add 8 g of citric acid, and stir for 50 minutes; A solution of 3 g of cerium nitrate, 2 g of praseodymium nitrate, 2 g of iron nitrate and 1.5 g of nickel nitrate was added dropwise at a rate of 0.5 mL / min, and stirring was maintained at 65°C.
[0050] S2: Coprecipitation Add 3g of ammonia water (25% concentration) and adjust the pH to 8.7; Keep stirring at 75 °C for 2 h to form a precipitate; Aging was carried out in a water bath at 55°C for 10 h.
[0051] S3: Drying and roasting Drying: Dry at 90℃ for 10h; Roasting: The first stage: calcination at 350℃ for 2h; The second stage: calcination at 750°C for 5 hours, introducing a 12% oxygen-nitrogen mixed gas.
[0052] S4: Wet ball milling After calcination, the pigment particles were wet-milled with ethylene glycol for 3 h and refined to 150 nm.
[0053] Summary: Based on Example 1, the rare earth doping and transition metal doping ratios were optimized (the rare earth doping amount was reduced to 3wt%, and the transition metal doping amount was increased to 4wt%), the aging time was extended (from 6h to 10h), and the calcination temperature was increased (350°C in the first stage and 750°C in the second stage), and pigment particles with a smaller particle size (150nm) were obtained. The crystal structure of the pigment is more stable, and the synergistic effect of rare earth and transition metal is enhanced, which significantly improves the light absorption performance and UV resistance of the pigment. At the same time, it has higher color saturation and durability, and is more suitable for coloring engineering plastics (such as PPS).
[0054] Embodiment 3: Material ratio: Barium titanate 83wt%, cerium nitrate 4wt%, praseodymium nitrate 3wt%, iron nitrate 4wt%, nickel nitrate 2wt%, citric acid 10wt%, ammonia water (25% concentration) 4wt%, and the balance deionized water.
[0055] Preparation process S1: Precursor solution preparation Dissolve 8.3 g of barium titanate in deionized water, add 10 g of citric acid, and stir for 60 minutes; A solution of 4 g of cerium nitrate, 3 g of praseodymium nitrate, 2 g of iron nitrate and 1 g of nickel nitrate was added dropwise at a rate of 0.8 mL / min, and the mixture was stirred at 70°C.
[0056] S2: Coprecipitation Add 4g of ammonia water (25% concentration) and adjust the pH to 8.9; Keep stirring at 80°C for 2 h to form a precipitate; Aging was carried out in a water bath at 60°C for 12 h.
[0057] S3: Drying and roasting Drying: Dry at 85℃ for 12h; Roasting: The first stage: calcination at 400℃ for 1h; The second stage: calcination at 800°C for 5 hours, with a 15% oxygen-nitrogen mixed gas introduced into the atmosphere.
[0058] S4: Wet ball milling After calcination, the pigment particles were wet-milled with ethylene glycol for 4 h and refined to 120 nm.
[0059] Summary: Based on Example 2, by further optimizing the atmosphere roasting conditions (a nitrogen mixture with 15% oxygen was introduced in the second stage of roasting) and increasing the roasting temperature to 800°C, a fade-resistant plastic pigment with a smaller particle size (120nm) and higher color vividness was prepared. The improved atmosphere roasting process significantly enhances the crystal phase stability and antioxidant properties of the pigment, allowing the pigment to maintain excellent color stability even when exposed to high temperature and ultraviolet light for a long time. The pigment is suitable for coloring plastics with higher high temperature resistance requirements (such as PEEK), and is particularly suitable for outdoor plastic products and UV-resistant plastic products.
[0060] Summary: Example 1 uses basic proportions and basic process parameters to prepare anti-fading plastic pigments that meet high temperature and UV stability requirements.
[0061] Example 2 optimizes the doping ratio, prolongs the aging time, and increases the calcination temperature to enhance the synergistic effect between rare earth and transition metal, thereby significantly improving the optical properties and stability of the pigment.
[0062] Example 3 further optimizes the atmosphere calcination conditions and temperature control, and improves the crystal phase stability and oxidation resistance performance, so that the pigment maintains color stability and brightness in more extreme environments.
[0063] Anti-fading plastic pigment performance verification experiment: Purpose: In order to more scientifically and systematically verify the actual effects of the pigment formulas and processes in Examples 1, 2, and 3, this experiment verifies the key properties of the pigments through multi-angle tests, including: High temperature processing performance: simulate the high temperature processing process of plastics and test the high temperature stability of pigments; Light aging resistance: UV aging test is used to verify the anti-fading performance of the pigment; Pigment dispersion performance: Test the dispersion of pigments in plastic matrix; Chemical stability: Test the stability of pigments in acidic, alkaline and oxidative environments; Color Performance: Measures color vividness and saturation.
[0064] Through experimental design and result analysis, the scientific basis for the optimized design of the embodiment is further explored.
[0065] Experimental content: Experimental design and samples: Experimental samples: The pigment prepared in Example 1; The pigment prepared in Example 2; The pigment prepared in Example 3.
[0066] Test dimensions and methods: High temperature stability: color change of pigments at high temperatures (400°C and 450°C); Anti-light aging performance: color change under long-term UV irradiation (0-2000h segmented test); Dispersion performance: the uniformity of the pigment dispersion in the plastic matrix; Chemical stability: Test the pigment in acid (pH=2), alkali (pH=12) and oxidant (3%H 2 O 2 ) Solubility and stability in the environment; Color Performance: Measuring Lab with Colorimeter * Parameter that evaluates color saturation.
[0067] Experimental steps: 1. High temperature stability test Sample preparation: Take 2 g of the pigment from each example and evenly apply it on the surface of an aluminum foil (the thickness is controlled to be 100 μm).
[0068] Experimental conditions: The samples were placed in a muffle furnace at 400°C and 450°C, respectively, and kept at a constant temperature for 4 hours.
[0069] Test method: Use a colorimeter to measure the color change (L * ,a * ,b * ), calculate the △E value (color change value).
[0070] Record the changes in color, morphology and gloss of the samples.
[0071] 2. Anti-light aging performance test Sample preparation: The pigment was mixed with a polypropylene (PP) matrix at a ratio of 2 wt% and prepared into a sheet (thickness 2 mm) by a twin-screw extruder.
[0072] Experimental conditions: Place the sample in a UV aging test box with a UV light intensity of 120W / m ² , temperature 55℃.
[0073] Continuous exposure time: 0, 500, 1000, 1500 and 2000h.
[0074] Test method: The color change (L * ,a * ,b * ) and △E value; The gloss change of the surface is measured by a gloss meter.
[0075] 3. Dispersion performance test Sample preparation: The pigment was mixed with polypropylene (PP) matrix at a ratio of 2 wt% and prepared into a film sample (thickness 100 μm) by a twin-screw extruder.
[0076] Experimental conditions: Under an optical microscope, observe the distribution of the pigment in the film; The number of pigment particles per square millimeter was counted and any agglomeration was noted.
[0077] 4. Chemical stability test Sample preparation: 1 g of each example pigment was placed in 10 mL of acidic (pH = 2), alkaline (pH = 12) and oxidizing (3% H 2 O 2 ) solution.
[0078] Experimental conditions: 60℃ constant temperature oscillation condition, treatment time 24h.
[0079] Test method: The dissolution rate was calculated by filtering and drying and weighing the residue; Observe the color change and measure the ΔE value.
[0080] 5. Color performance test Sample preparation: The pigment was mixed with polypropylene matrix at a ratio of 2wt% to prepare sheet samples.
[0081] Test method: Use a colorimeter to measure the L * ,a * ,b * value; Calculates color saturation and vividness.
[0082] Experimental results data: 1. High temperature stability test results Example Test temperature L* value change a* value changes b* value change △E value Surface gloss changes Example 1 400℃ 3.2→3.7 1.1→1.5 5.5→6.1 1.02 Slight gloss reduction Example 2 400℃ 3.0→3.4 1.2→1.4 5.4→5.7 0.72 Slight change in gloss Example 3 400℃ 2.9→3.1 1.0→1.1 5.2→5.3 0.35 No significant change in gloss Example 1 450℃ 3.2→3.9 1.1→1.8 5.5→6.5 1.56 Obvious reduction in gloss Example 2 450℃ 3.0→3.6 1.2→1.5 5.4→6.0 1.08 Slightly reduced gloss Example 3 450℃ 2.9→3.2 1.0→1.2 5.2→5.4 0.48 No significant change in gloss 2. Anti-light aging performance test results Example Exposure time (h) L* value change a* value changes b* value changes △E value Gloss changes Example 1 2000 3.2→4.0 1.1→1.8 5.5→6.6 1.80 The surface is obviously white Example 2 2000 3.0→3.6 1.2→1.5 5.4→6.0 1.14 Slightly white surface Example 3 2000 2.9→3.2 1.0→1.1 5.2→5.3 0.62 No obvious changes on the surface 3. Dispersion performance test results Example Average number of pigment particles (pcs / mm2) Number of agglomeration phenomena Dispersion evaluation Example 1 35 5 good Example 2 42 3 good Example 3 50 1 excellent 4. Chemical stability test results Example Solution environment Dissolution rate (%) △E value Chemical stability evaluation Example 1 pH=2 1.5 1.20 General stability Example 2 pH=2 0.9 0.88 Good stability Example 3 pH=2 0.5 0.42 Excellent stability Example 1 pH=12 2.1 1.50 General stability Example 2 pH=12 1.2 1.05 Good stability Example 3 pH=12 0.6 0.55 Excellent stability 5. Color performance test results Example Color Saturation Color Vibrance Comprehensive evaluation Example 1 75 78 good Example 2 82 85 good Example 3 90 92 excellent Experimental summary: High temperature stability: Example 3 has the strongest high temperature stability, with the color change values (△E) being the smallest at 400°C and 450°C, and the gloss being the best.
[0083] Light aging resistance: Example 3 has significantly better color retention under UV exposure than other examples (△E=0.62), and is suitable for outdoor and UV-resistant plastic products.
[0084] Dispersion performance: Example 3 has excellent dispersibility, and the particles are evenly distributed without obvious agglomeration.
[0085] Chemical stability: Example 3 has the best chemical stability, the lowest dissolution rate in acid, alkali and oxidizing environments, and the smallest ΔE value.
[0086] Color performance: The color saturation and vividness of Example 3 are significantly higher than those of other examples.
[0087] Overall conclusion: Example 3 is superior to Example 1 and Example 2 in terms of high temperature stability, light aging resistance, dispersibility, chemical stability and color performance, proving that its optimized design and process have a significant performance improvement effect and are suitable for the coloring needs of high-end plastic products.
[0088] Comparative experiment: Performance comparison experiment between the pigment of the present invention and traditional pigments Purpose: This experiment aims to verify the significant performance advantages of the pigment of the present invention (Example 3) by comprehensively testing and comparing the pigment of the present invention (Example 3) with a variety of traditional pigments (inorganic pigments, organic pigments, composite pigments) in five dimensions: high temperature stability, UV aging resistance, dispersion performance, chemical stability, and color performance. The experiment further clarifies the industrial application value of the pigment of the present invention, especially its potential in the field of engineering plastics and outdoor plastic products.
[0089] Sample Description: 1. Pigment of the present invention Sample features: Based on the barium titanate lattice system, using rare earth ions (Ce 3+ , Pr 3+ ) and transition metal ions (Fe 3+ 、Ni 2+ ) synergistic doping optimization, the particle size is about 120nm, and it has excellent high temperature stability and UV resistance.
[0090] By optimizing the calcination atmosphere (15% oxygen and nitrogen mixture) and dispersion process, the uniformity of the pigment dispersion in the plastic matrix is ensured.
[0091] Applicable scenarios: Coloring of high-temperature plastics (such as PEEK), engineering plastics (such as PPS), outdoor plastic products and UV-resistant plastic products.
[0092] 2. Red iron oxide (traditional inorganic pigment) Sample characteristics: A common iron oxide-based inorganic pigment with good high temperature resistance, high chemical stability, and a particle size of about 200nm.
[0093] However, due to the uneven particle morphology, the dispersion is average and the color brightness is low.
[0094] Applicable scenarios: used for coloring building materials and ordinary plastic products.
[0095] 3. Phthalocyanine blue (traditional organic pigment) Sample characteristics: Commonly used for coloring plastics, inks and coatings, with high color brightness and a particle size of about 300nm.
[0096] However, it is easy to decompose under high temperature conditions, has poor UV resistance and poor chemical stability.
[0097] Applicable scenarios: Used for coloring low-temperature plastics and decorative plastic products.
[0098] 4. Chrome oxide green and organic azo composite pigment (traditional composite pigment) Sample characteristics: Inorganic pigments (chrome oxide green) and organic pigments (azo pigments) are compounded to improve color performance, and the particle size is about 250nm.
[0099] It has a certain degree of high temperature stability and color vividness, but its chemical stability is average.
[0100] Applicable scenarios: used for multifunctional coating materials and decorative plastics.
[0101] Experimental content: Experimental design and dimensions: The experiments focus on the following five performance dimensions: High temperature stability: color change of pigments at 400°C and 450°C; Anti-UV aging performance: evaluate color fading and surface gloss changes through long-term exposure to UV light; Dispersion performance: Test the uniformity of pigment particle distribution in polypropylene (PP) matrix; Chemical stability: evaluates the solubility and color stability of pigments in acidic, alkaline and oxidative environments; Color Performance: Measures color saturation and vividness.
[0102] Experimental steps: 1. High temperature stability test Purpose: To evaluate the thermal stability of pigments during high temperature plastic processing.
[0103] step: Take 2g of each pigment and evenly apply it on the surface of the aluminum foil (coating thickness 100μm).
[0104] The samples were placed in a muffle furnace at 400°C and 450°C for 4 h.
[0105] The color parameters (L * ,a * ,b * ), calculate the △E value (the smaller the △E, the smaller the color change).
[0106] Observe and record changes in color, morphology and gloss of the pigment surface.
[0107] 2. Anti-ultraviolet aging performance test Purpose: To verify the ability of pigments to resist fading under long-term UV radiation.
[0108] step: Each pigment was mixed with polypropylene (PP) at a ratio of 2 wt % and prepared into a sheet (thickness 2 mm) by a twin-screw extruder.
[0109] Place the sample in a UV aging test chamber (UV light intensity 120W / m 2 , temperature 55℃), continuous exposure 2000h.
[0110] The color parameters of the samples were recorded every 500 hours (L * ,a * ,b * ) and surface gloss changes.
[0111] Calculate the △E value at each time period to evaluate the color fading.
[0112] 3. Dispersion performance test Purpose: To test the uniformity of pigment distribution in plastic matrix.
[0113] step: Each pigment was mixed with polypropylene (PP) at a ratio of 2 wt % to prepare a film sample with a thickness of 100 μm.
[0114] The distribution of pigment particles in the film was observed under an optical microscope, and the number of particles per square millimeter was recorded.
[0115] Count the number of particle agglomeration phenomena and evaluate the dispersion performance.
[0116] 4. Chemical stability test Purpose: To evaluate the solubility stability of pigments in acidic, alkaline and oxidative environments.
[0117] step: 1 g of each pigment was placed in 10 mL of acidic (pH = 2), alkaline (pH = 12) and oxidizing (3% H 2 O 2 ) solution.
[0118] Treat at 60°C with constant temperature shaking for 24 h.
[0119] The mass of the pigment residue was weighed after filtering and drying, and the dissolution rate was calculated; Measuring color parameters (L * ,a * ,b * ) changes and calculate the △E value.
[0120] 5. Color performance test Purpose: To evaluate the color brightness and saturation of pigments.
[0121] step: Each pigment was mixed with polypropylene at a ratio of 2 wt % to prepare a sheet sample.
[0122] Using a colorimeter to measure L * ,a * ,b * Values, calculate color saturation and vividness.
[0123] Experimental results data: 1. High temperature stability test results pigment Test temperature L* value change a* value changes b* value changes △E value Gloss changes Pigment of the present invention 400℃ 2.9→3.1 1.0→1.1 5.2→5.3 0.48 No significant change in gloss Iron oxide red 400℃ 3.0→3.3 1.2→1.5 5.4→5.8 0.72 Slight gloss reduction Phthalocyanine blue 400℃ 3.5→4.0 1.5→2.2 5.7→6.5 1.82 Significant reduction in gloss Composite pigments 400℃ 3.3→3.8 1.3→1.8 5.6→6.3 1.20 The gloss is reduced 2. Anti-ultraviolet aging performance test results pigment Exposure time (h) L* value change a* value changes b* value change △E value Gloss changes Pigment of the present invention 2000 2.9→3.2 1.0→1.2 5.2→5.3 0.62 No significant change in gloss Iron oxide red 2000 3.0→3.8 1.2→1.8 5.4→6.1 1.28 Slightly reduced gloss Phthalocyanine blue 2000 3.5→5.0 1.5→2.5 5.7→7.0 2.58 Significantly reduced gloss Composite pigments 2000 3.3→4.5 1.3→2.2 5.6→6.8 1.92 The gloss is reduced Experimental summary: High temperature stability: The pigment of the present invention has the smallest color change at 400°C and 450°C (ΔE is 0.48 and 0.62 respectively), which is much better than traditional pigments.
[0124] Anti-ultraviolet aging performance: In a 2000h ultraviolet aging experiment, the △E value of the pigment of the present invention is only 0.62, and there is almost no fading, while phthalocyanine blue (△E=2.58) fades the most seriously.
[0125] Dispersion performance: The particle distribution of the pigment of the present invention is the most uniform, and agglomeration occurs only once, and the dispersion is evaluated as excellent.
[0126] Chemical stability: The dissolution rate of the pigment of the present invention is the lowest in acid, alkali and oxidative environments, showing excellent chemical stability.
[0127] Color performance: The color saturation and brightness of the pigment of the present invention are higher than those of inorganic pigments and composite pigments, and slightly lower than that of phthalocyanine blue, but the overall performance is the best.
[0128] Overall conclusion: The pigment of the present invention is superior to traditional pigments in terms of high temperature stability, UV resistance, dispersibility and chemical stability. It is suitable for coloring high-performance plastics and outdoor products and has significant industrial application value.
[0129] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A fade-resistant plastic pigment, characterized in that: Calculated by weight percentage, it includes the following components: 70%-90% tungstate or titanate, 3%-10% rare earth doping ions, 2%-8% transition metal doping ions, 5%-15% citric acid, 1%-5% ammonia water, and the rest is solvent deionized water.
2. The anti-fading plastic pigment according to claim 1, characterized in that: The tungstate is sodium tungstate, and the titanate is barium titanate.
3. The anti-fading plastic pigment according to claim 1, characterized in that: The rare earth doping ions are cerium nitrate and praseodymium nitrate, and the transition metal doping ions are iron nitrate and nickel nitrate.
4. The anti-fading plastic pigment according to claim 1, characterized in that: The rare earth doping ions and transition metal doping ions are mixed in a molar ratio of 1:1, and the total doping amount is 5%-10% of the total molar amount of tungstate or titanate.
5. A method for preparing an anti-fading plastic pigment, characterized in that: The following steps are involved: S1. Preparation of precursor solution: dissolve tungstate or titanate in deionized water, add citric acid chelating agent, stir for 50-60 minutes to form a basic solution, slowly add rare earth doping ion and transition metal doping ion solution, and stir evenly; S2, co-precipitation: add ammonia water to the mixed solution, adjust the pH to 8.5-9.0, control the temperature to 70-80°C, form a precipitate, and age the precipitate for 6-12 hours; S3, drying and calcining: drying the precipitate to form a precursor powder, which is then calcined in two stages to form the final pigment particles; S4. Pigment preparation: The calcined pigment particles are refined to 100-500 nm by wet ball milling, the ball milling medium is ethylene glycol, and the ball milling time is 2-4 hours.
6. The method for preparing a fade-resistant plastic pigment according to claim 5, characterized in that: In the process of preparing the precursor solution in step S1, the rare earth doping ion solution and the transition metal doping ion solution are added to the base solution in a dropwise manner, with a dropwise acceleration rate of 0.5-1 mL / min and a stirring temperature of 60-70°C.
7. The method for preparing a fade-resistant plastic pigment according to claim 5, characterized in that: In the co-precipitation step of step S2, the concentration of the aqueous ammonia solution is 20-25%, and the precipitation aging is carried out in a water bath at 50-60°C.
8. The method for preparing a fade-resistant plastic pigment according to claim 5, characterized in that: The drying in step S3 is carried out at 80-90° C. for 10-12 hours.
9. The method for preparing a fade-resistant plastic pigment according to claim 5, characterized in that: The roasting step S3 includes: The first stage: calcination at 300-400℃ for 1-2h; The second stage: calcining at 700-800℃ for 4-5h, while introducing a 10%-15% oxygen and nitrogen mixed gas.
10. The anti-fading plastic pigment according to any one of claims 1 to 4, characterized in that: The pigment is used for high-temperature processing coloring of polypropylene, polyamide, polyphenylene sulfide, and polyetheretherketone-based plastics and coloring of ultraviolet-resistant plastic products.